A dye-sensitized solar cell model implementable in electrical circuit simulators - Afonso Lopes (2015)
The main goal of the present work is to provide a mathematical model of Dye-Sensitized Solar Cells (DSCs) that can be implementedin electrical engineering circuit simulation software, such as PSIM, for using in electronic power converter design. Consequently, a newcircuit modeling approach is presented, able to solve the standard continuity and transport governing equations defined for the involvedmobile species: electrons in the TiO2 conduction band and ions in the electrolyte. Starting from the partial differential continuityequations of the phenomenological DSC model, it was developed a one-dimensional spatial discretization using Finite DifferenceMethods (FD) followed by a solution using an electrical circuit analogy. The resulting circuits were then implemented in PSIM softwareand simulated. Simulation results using this new electrical analog approach showed excellent matching when compared to FORTRANnumerical solutions, as well as when compared to experimental data. Moreover, the electrical analog can be used for transient and steadystate cases, giving information about the main factors and the relevant kinetic parameters that influence DSCs' performance. Finally, itenables to relate the phenomenological behavior with other electrical approaches, such as Electrochemical Impedance Spectroscopy(EIS) and diode based models.